Hello there!
The correct answer is option B (-3,3)
-3x - y = 6
-3(-3) - 3 = 6
9 - 3 = 6
6 = 6
Thus, the correct answer is option B
Good luck with your studied!
Answer:
![x_{1} =-3 +\sqrt{14} \\\\x_{2} =-3 -\sqrt{14}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D-3%20%2B%5Csqrt%7B14%7D%20%5C%5C%5C%5Cx_%7B2%7D%20%3D-3%20-%5Csqrt%7B14%7D)
Step-by-step explanation:
+6x-5=0
we divide the coefficient of the X by half :
in this case: 6/2 = 3 , then we do the following
The result obtained is raised to square power: 3^2=9
we sum and subtract by 9 to maintain the balance of the equation:
+6x+9-9-5=0
we have:
-9-5=0
= 14
lets apply square root on both sides of the equation:
![\sqrt{(x+3)^{2}}=\sqrt{14}](https://tex.z-dn.net/?f=%5Csqrt%7B%28x%2B3%29%5E%7B2%7D%7D%3D%5Csqrt%7B14%7D)
we know:
![\sqrt{a^{2}} = abs(a)](https://tex.z-dn.net/?f=%5Csqrt%7Ba%5E%7B2%7D%7D%20%3D%20abs%28a%29)
so we have:
abs(x+3)=![\sqrt{14}](https://tex.z-dn.net/?f=%5Csqrt%7B14%7D)
from where two solutions are obtained
![x_{1} + 3 =\sqrt{14} \\\\x_{2} + 3 =-\sqrt{14}](https://tex.z-dn.net/?f=x_%7B1%7D%20%2B%203%20%3D%5Csqrt%7B14%7D%20%5C%5C%5C%5Cx_%7B2%7D%20%2B%203%20%3D-%5Csqrt%7B14%7D)
finally we have:
![x_{1} =-3 +\sqrt{14} \\\\x_{2} =-3 -\sqrt{14}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D-3%20%2B%5Csqrt%7B14%7D%20%5C%5C%5C%5Cx_%7B2%7D%20%3D-3%20-%5Csqrt%7B14%7D)
Answer:
Given,
A=90
b=15
A=12bh
Now,
Step-by-step explanation:
Put the given value in the formula
A=12bh
90=12*15*h
90=180h
90/180=h
Hence, h=0.5
Answer:
Right angled triangle
Step-by-step explanation:
This is because the square root of the sum of the squares of 7 and 24 is 25 ( Pythagoras theorem) . This only works for right angled triangle.